2017 14th IAPR International Conference on Document Analysis and Recognition (ICDAR) 2017
DOI: 10.1109/icdar.2017.145
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Text Detection in Born-Digital Images via Fully Convolutional Networks

Abstract: Traditional layout analysis methods cannot be easily adapted to born-digital images which carry properties from both regular document images and natural scene images. One layout approach for analyzing born-digital images is to separate the text layer from the graphics layer before further analyzing any of them. In this paper, we propose a method for detecting text regions in such images by casting the detection problem as a semantic object segmentation problem. The text classification is done in a holistic app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Research on text extraction such as Morris et al [4] and Nayef & Logier [5] has shown that even noiseless born-digital images are sometimes better analyzed with neural nets than with handcrafted features and heuristics. Born-digital and educational images need further benchmarks related to challenging information retrieval tasks in order to test the generalization of methods for those tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Research on text extraction such as Morris et al [4] and Nayef & Logier [5] has shown that even noiseless born-digital images are sometimes better analyzed with neural nets than with handcrafted features and heuristics. Born-digital and educational images need further benchmarks related to challenging information retrieval tasks in order to test the generalization of methods for those tasks.…”
Section: Introductionmentioning
confidence: 99%